Implementation of the Project for Strengthening the Profile of Pancasila Students from a Local Wisdom Perspective - Lestari, Icha Suci; Adi, Panggih Nur; Saragih, Siti Zahara; Hubi, Zindan Baynal (CV. Rayyan Dwi Bharata, 2025)
This study aims to determine the implementation, form, and positive impact of the implementation of P5 in the perspective of local wisdom. This research method uses literature review. This process is carried out by gathering, reading, analyzing, and developing relevant literature. The results of this study are that the definition of the Pancasila Student Profile is the implementation of national education goals to realize humans with the character of Pancasila and develop the potential of students. Dimensions in the Pancasila Student Profile there are six kinds, namely devoted to God Almighty, creative, mutual cooperation, global diversity, independent, and critical reasoning, while the principles of the Pancasila student profile are holistic, centralized, exploratory, and contextual. Some P5 themes are local wisdom, build their body and soul, Unity in Diversity, Technology Engineering, Democracy, and Entrepreneurship. In the perspective of local wisdom, the form of P5 is the making of written batik, the tradition of the offerings, and the earth's tradition. The positive impact of P5 in the theme of local wisdom is to know the local culture, form positive characters, uphold harmony and harmonization, and avoid ethnocentrism attitudes.